Mechanisms and inhibitors of ferroptosis in psoriasis - Zhou, Qiao; Yang, Lijing; Li, Ting; Wang, Kaiwen; Huang, Xiaobo; Shi, Jingfen; Wang, Yi (Frontiers in Molecular Biosciences, 2022)
Psoriasis is a chronic inflammatory skin disease that features localized or widespread erythema, papules, and scaling. It is common worldwide and can be distributed throughout the whole body. The pathogenesis of psoriasis is quite complex, which is the result of the interplay of genetic, environmental and immune factors. Ferroptosis is a kind of iron-dependent programmed death, which is different from cell senescence, apoptosis, pyroptosis and other forms of cell death. Ferroptosis involves three core metabolites: iron, lipids, and reactive oxygen species (ROS). It is primarily driven by lipid peroxidation. As an effective inhibitor of lipid peroxidation, ferrostatin-1 (Fer-1) can inhibit the changes that are related to ferroptosis in erastin-treated keratinocytes and block the inflammatory responses. Therefore, it has a certain effect on the treatment of psoriatic lesions. Although ferroptosis is closely associated with a variety of human diseases such as the inflammatory diseases, no review focused on the psoriasis with ferroptosis. In this mini review, we mainly focus on the pathogenesis of psoriasis, the mechanisms of ferroptosis, the connection between ferroptosis and psoriasis and ferroptosis inhibitors in psoriasis treatment. We simultaneously provide recent research advances and the perspectives on relations between ferroptosis and psoriasis.